(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The research explores the possibilities of biogas extraction from aquaculture waste. Samples of fish-farming pool sludge were taken from a fish farm, which is located in the Krāslava district, Kalnieši rural municipality. Prior to experimental fermentation and extraction of biogas, samples were analyzed in order to determine their moisture and organic matter content (OMC). For purpose of increasing OMC available for fermentation, sludge was mixed with crushed reeds. Biogas was obtained from the samples at various ratios of sludge and reed residues. During the experiments, 3.81 liters of biogas were obtained from a mixture of fish-farming pool sludge and crushed reed at reed mass 100 g. The results of experimental research indicate that aquaculture residues can be used to produce biogas.